Pengembangan Model Pengukuran Kinerja Pusat Investasi Perusahaan dengan Menggunakan Sistem Agen Cerdas - Azhari Azhari; Eko Rahman Wisuda (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2007)
This research presents on development of an intelligent agent system model which is used to measureperformance of company investment center. We apply EVA (Economic Value Added) and ROI (Return OnInvestment) measurement approach to our agent capability system. We named our agents such as Agen_data,Agen_ukur, and Agen_keputusan. Based on some empirical data for examining show that our agents capablecalculating autonomously EVA and ROI values, and preparing initial conclution whether the company is gainingprofit, or suffer a financial loss. These agents can also recognize and inform the return level from investedcapital so the company will know whether this invested capital can produce profit or loss. According thisresearch we conclude the system easy to use, and the responsibility of center managers will be easy to measure,grade, and analysis the goal of achievement from each manager.Keywords: Intelligent agents, company invesment center, invesment performance, EVA, ROI.